Diversity of Picea omorika (Pančić) Purk. Populations Based on Morpho-anatomical Needle Traits and Bioclimatic Parameters - Biljana Nikolić; Nemanja Rajčević; Zorica Mitić; Sanja Jovanović; Nevena Čule; Katarina Mladenović; Marija Marković; Petar Marin (South-East European Forestry, 2024)
Picea omorika (Pančić) Purkyne is a well-known endemic conifer species. However, there have been few morpho-anatomical studies to date. Several years ago, preliminary population studies of P. omorika were published, but with the inclusion of additional populations, it became necessary to confirm whether the southernmost population from Mileševka Canyon, also known as var. vukomanii, (Pavlović and Matović 1994), remains distinct from the others. Two-year-old needles from the lower third of the crown were collected in late autumn from seven natural populations of P. omorika from Serbia and from the border with Bosnia and Herzegovina. The variability of ten morpho-anatomical traits and the cross-sectional anatomy of Serbian spruce needles were examined in seven natural populations in Serbia. Needle length was measured with a digital calliper, and the nine other needle traits, needle width, needle thickness, vascular bundle diameter, resin ducts diameter, number of resin ducts, distance between vascular bundle and resin duct, cuticle and epidermal thickness, hypodermal thickness, and hypodermal width, were examined under a light microscope. For most of the traits studied, the Štula population had the highest values, whereas the Bilo population had the lowest. Needles with triangular sections are most common in the southern part of Mt. Tara, while elliptical and rhomboidal sections are characteristic in populations at the edge of the distribution range in Serbia. Multivariate analyses separated populations into two main groups. Both principal component analysis and discriminant analysis indicated population overlap, while cluster analysis identified three main groups. Multivariate analysis of bioclimatic data and a correlation study of morpho-anatomical traits were also performed. Based on bioclimatic parameters, individuals in the populations from Mileševka and Štula showed the most distinct characteristics. Mantel and partial Mantel tests confirmed no correlation between the complete set of morphological traits and bioclimatic parameters, even after adjusting for regional differences.